2018
DOI: 10.15275/rusomj.2018.0204
|View full text |Cite
|
Sign up to set email alerts
|

The immune response mediator genes polymorphic variants as predictors of the etanercept efficacy in juvenile idiopathic arthritis

Abstract: Objective-The aim of the study was to investigate the relationship of the alleles and genotypes of the immune response mediator genes polymorphic loci (rs1800629, rs909253, rs16944, rs6822844, rs2104286, rs1800795, rs1800872, rs3087243, rs755622 rs28362491, rs2240336, rs2476601) with the etanercept efficacy in juvenile idiopathic arthritis (JIA) patients. Material and Methods-The study included 39 JIA patients from Bashkortostan, Russia. Achieving the American College of Rheumatology Pediatric 70 (ACR Pedi 70)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…At the same time, an increased proinflammatory cytokine production in the NFKB1 rs28362491*D allele carriers may suggests a good effect of an anticytokine therapy. This hypothesis is confirmed by the data of Nazarova et al (2018), according to which the NFKB1 rs28362491*D allele reduces the risk of nonachieving the ACR Pedi 70 response to etanercept in JIA patients [33]. At the same time, in the present work it was shown that the NFKB1 rs28362491*DD genotype marks an increased susceptibility to the nonresponse to methotrexate in JIA (in girls).…”
Section: Response To Methotrexatesupporting
confidence: 90%
See 1 more Smart Citation
“…At the same time, an increased proinflammatory cytokine production in the NFKB1 rs28362491*D allele carriers may suggests a good effect of an anticytokine therapy. This hypothesis is confirmed by the data of Nazarova et al (2018), according to which the NFKB1 rs28362491*D allele reduces the risk of nonachieving the ACR Pedi 70 response to etanercept in JIA patients [33]. At the same time, in the present work it was shown that the NFKB1 rs28362491*DD genotype marks an increased susceptibility to the nonresponse to methotrexate in JIA (in girls).…”
Section: Response To Methotrexatesupporting
confidence: 90%
“…In addition to the experimental features, these differences can also be associated with the samples characteristics, in particular with the sex ratio, since in the present work it has been shown that the IL1B rs16944*T allele increases the risk of the insufficient response to methotrexate only in boys with JIA. It should also be noted that the relationship of the IL1B rs16944*TT genotype with the nonachieving of the ACR Pedi 70 response to etanercept in JIA was previously established, which is important to consider when selecting the second-line therapy for these patients [33].…”
Section: Response To Methotrexatementioning
confidence: 99%
“…Our meta-analysis of the most replicated polymorphism of TNF-α promoter, genotyped in an overall population of 414 JIA, showed that the presence of rare A allele at position −308 was definitely associated with treatment outcome postulating a dominant model and on average doubling the risk of nonresponse to TNF-α drugs. However, at an individual level, only one study reached the statistical significance unambiguously, 10 whereas 3 studies showed only a trend 9,11,12 and the last 2 did not find any association 13 or even an inverse association 8 . These inconsistencies are coherent with the characteristics of each study: low precision in the estimates can be explained by the low number of patients included in the study, the strength of association depends also on the proportion of responder/nonresponder patients, and this ratio can be affected by the study design (prospective vs retrospective), as potential bias could be introduced through the selection process.…”
Section: Discussionmentioning
confidence: 89%
“…1). [6][7][8][9][10][11][12][13] Comparing the current search with the previous review, 4 5 new articles were identified that investigated the potential effect of genetic variants on response to TNF-α blocking agents in JIA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation